D-dimer concentrations in dogs with kidney disease with or without protein-losing nephropathy. (September 2016) - Roumpeas, Efstathios; Kostoulas, Polychronis; Polizopoulou, Zoe; Koutinas, Christos; Mylonakis, Mathios
Abstract Limited information is currently available regarding the range of D-dimer concentrations in dogs with kidney disease (KD). The objective of the present cross-sectional study was to investigate the concentration of D-dimers in dogs with KD irrelevant of the underlying cause or the time course of the KD and the potential association of D-dimers elevation with serum creatinine concentration, concurrent protein-losing nephropathy (PLN) or the age of the animals. D-dimers were measured by a semi-quantitative plasma latex agglutination assay in 31 healthy dogs (group A) and in 30 dogs with KD (group B), without evidence of concurrent extra-renal disease that may precipitate hypercoagulation. Significantly higher median D-dimer concentrations (p = 0.0133) and a higher prevalence of increased D-dimers (≥250 μg/L) (p = 0.011) were documented in dogs with KD as compared to healthy dogs, and the increased D-dimers were not associated with the serum creatinine concentration, the coexistent PLN or the age of the dogs. In conclusion, the detection of increased D-dimers in the context of impaired kidney function should be cautiously interpreted in the dog and should not be invariably assumed to imply the presence of a state of hypercoagulability.